Antimicrobial Efficacy and Biocompatibility of a Denture Cleanser Containing Paeonia lactiflora Extract - Ji-Won Lim; Jiyeon Lee; Min-Kyung Kang; Hee-Eun Kim (Biomedicines)
Background/Objectives: Microbial biofilms on denture surfaces pose significant oral and systemic health risks. Although chemical denture cleansers are widely used, they can cause mucosal irritation and disrupt the oral microbiome. The aim of this study was to evaluate the antimicrobial efficacy and biocompatibility of a denture cleanser containing Paeonia lactiflora extract (DC-PL) as a potential natural alternative. Methods: Oral microcosm biofilms were formed using human saliva and matured over 6 days. Then, the biofilms were treated for 1 min daily over 6 days with DC-PL, distilled water (DW; negative control), or Polident® (PD; positive control). Antimicrobial effects were assessed by measuring the red fluorescence intensity (ratio of red to green fluorescence intensity [RatioR/G]) and aciduric bacterial counts. Biocompatibility was evaluated through an oral mucosal irritation test. A one-way analysis of variance followed by Tukey’s post hoc test was used for between-group comparisons. Results: RatioR/G in the DC-PL group was significantly lower than that in the DW group (0.94-fold, p = 0.021) and comparable with that in the PD group (p = 0.502). Aciduric bacterial counts in the DC-PL group were 0.92-fold lower than those in the DW group (p = 0.037) and comparable with those in the PD group (p = 0.460). The oral mucosal irritation index was 0, indicating no irritation. Conclusions: DC-PL demonstrated antimicrobial efficacy similar to that of PD while maintaining excellent biocompatibility. These findings underscore its potential as a safe and effective alternative to conventional chemical cleansers, offering a clinically viable solution for improving oral health management.